TECHNOLOGY AND ECONOMIC DEVELOPMENT: RETROSPECTIVE - Nikoloski, Krume (Journal of process management and new technologies, 2016)
The purpose of this paper is to represent historical link between technological progress and economic development. Furthermore, the reasons are aimed at presenting the stages of development of technological progress and its contribution to economic development, particularly in changing economic and social life. I want to emphasize that many researchers of scientific thought, technological progress has been learned as one of the root causes of cyclical movement of capitalist economy. Others seek to quantify the share of technological progress in the rate of GDP growth. Also, in this paper are going to be analyzed the importance of technological progress in society and will be given a chronological framework for the role and importance of the scientific and technological revolutions.